2004
DOI: 10.1128/aem.70.2.837-844.2004
|View full text |Cite
|
Sign up to set email alerts
|

A New Alkali-Thermostable Azoreductase from Bacillus sp. Strain SF

Abstract: A screening for dye-decolorizing alkali-thermophilic microorganisms resulted in a Bacillus sp. strain isolated out of the wastewater drain of a textile finishing company. An NADH-dependent azoreductase of this strain, Bacillus sp. strain SF, was found to be responsible for the decolorization of azo dyes. This enzyme was purified by a combination of ammonium sulfate precipitation and anion-exchange and affinity chromatography and had a molecular mass of 61.6 kDa and an isoelectric point at pH 5.3. The pH optimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(112 citation statements)
references
References 37 publications
4
103
1
4
Order By: Relevance
“…Two broad types of azoreductases including flavin-dependent and non-flavin reductases have been reported (Blumel & Stolz, 2003;Maier et al, 2004;Suzuki et al, 2001). Flavin-dependent azoreductases usually reduce azo dyes through a Ping-Pong Bi-Bi mechanism (Nakanishi et al, 2001;Ryan et al, 2010;Wang et al, 2010).…”
Section: Reductive Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two broad types of azoreductases including flavin-dependent and non-flavin reductases have been reported (Blumel & Stolz, 2003;Maier et al, 2004;Suzuki et al, 2001). Flavin-dependent azoreductases usually reduce azo dyes through a Ping-Pong Bi-Bi mechanism (Nakanishi et al, 2001;Ryan et al, 2010;Wang et al, 2010).…”
Section: Reductive Enzymesmentioning
confidence: 99%
“…The azoreductases are classified into two groups on the basis of their electron donor requirements. The first includes flavin containing azoreductases, which show preference for NADH, while the second performs better with NADPH as a reductant for azo dye decolorization (Chen et al, 2005;Maier et al, 2004;Punj & John, 2008). Burger & Stolz (2010) isolated a flavin free azoreductase enzyme from Xenophilus azovorans KF46F strain.…”
Section: Reductive Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been reported that very few strains can withstand the conditions of dyeing effluents (Maier, 2004). Thus, as a preliminary step in the development of textile waste effluents biotreatment process involving indigenous microbial species, the present study have shown that Aspergillus niger, Pseudomonas fluorescence, Proteus morganii, Fusarium compacticum, Pseudomonas nigificans and Pseudomonas gellucidium, respectively, has a significant potential for dye decolourization and degradation.…”
Section: Resultsmentioning
confidence: 81%
“…The treatment of textile waste effluents is still a major environmental concern because of synthetic dyes which are difficult to be removed by conventional physical and chemical technologies (Zhang et al, 2004) such as membrane filtration, coagulation, precipitation, flotation, adsorption, ion exchange, chemical reduction, ultrasonic mineralization, electrolysis and advanced chemical oxidation (Gogate and Pandit, 2004;Kang et al, 2010). Some of these methods are effective but have inherent drawbacks such as high cost, intensive energy requirements, formation of hazardous by-products and generation of sludge which causes secondary pollution (Do et al, 2002;Verma et al, 2003;Maier et al, 2004;Ramya et al, 2007;Dayaram and Dasgupta, 2008). Current available treatment technologies have been reviewed by Robinson ) and specific attention is given to biological treatment processes because they are cost-effective and environmentally friendly.…”
mentioning
confidence: 99%